2012
DOI: 10.1080/14786419.2010.533666
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds fromScorzonera latifolia(Fisch. & Mey.) DC.

Abstract: A new 3-benzylphthalide, scorzoveratrin 4'-O-β-glucoside (1), together with the known 3-benzylphthalides, scorzoveratrin (2) and scorzoveratrozit (3), the caffeoyl derivatives, chlorogenic acid methyl ester (4), 4,5-dicaffeoylquinic acid (5), 4,5-dicaffeoylquinic acid methyl ester (6), 3,5-dicaffeoylquinic acid (7) and caffeic acid (8) were isolated from the subaerial parts of Scorzonera latifolia (Fisch. & Mey.) DC. All secondary metabolites were assigned using physicochemical and spectroscopic data. The know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The molecular formula was determined as Scorzonera parviflora has been evaluated for their inhibitory activities of TNF-α and IL-1β production, and NF-κB nuclear translocation in THP-1 macrophages and HPLC analysis revealed chlorogenic acid was present in all tested extracts [32]. Isolation of caffeic acid derivatives was mentioned from the subaerial parts of S. latifolia [33].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular formula was determined as Scorzonera parviflora has been evaluated for their inhibitory activities of TNF-α and IL-1β production, and NF-κB nuclear translocation in THP-1 macrophages and HPLC analysis revealed chlorogenic acid was present in all tested extracts [32]. Isolation of caffeic acid derivatives was mentioned from the subaerial parts of S. latifolia [33].…”
Section: Resultsmentioning
confidence: 99%
“…According to the current study Scorzonera root extracts displayed hepatoprotective activities probably due to their chlorogenic acid contents. Derivatives of chlorogenic acid 3,4 and 3,5 dicaffeoylquinic acids were also reported to have protective activity in CCl 4 induced hepatotoxicity [26] which have also been isolated from some Scorzonera species previously [11,12] .…”
Section: Resultsmentioning
confidence: 99%
“…Antiinflammatory, antioxidant, and wound healing activities have also been reported [6][7][8][9] . Phytochemical analyses revealed that S. latifolia roots contained taraxasteryl myristate, taraxasteryl acetate, motiol, 3-β-hydroxy fern-8 en-7-one acetate, urs-12-en-11-one-3-acetyl, 3-β-hydroxyfern-7-en-6-one-acetate, olean-12-en-11-one-3-acetyl, fern-7-en-3-β-one, leucodin, β-sitosterol [3,5,10] , chlorogenic acid, chlorogenic acid methyl ester, 1,5-dicaffeoyl quinic acid, 3,5-dicaffeoyl quinic acid, methylester of 3,5-dicaffeoyl quinic acid, hydrangenol-8-O-β-glucoside, hydrangenol-4'-O-β-glucoside, scorzotomentosin-4'-O-β-glucoside and a new isocoumarine derivative [11] as well as scorzoveratrin 4'-O-β-glucoside, scorzoveratrin, scorzoveratrozit, 4,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid methyl ester and caffeic acid [12] . Scorzotomentosin, scorzotomentosin-4'-O-β-glucoside, scorzophtalide, scorzoerzincanin, hydrangenol, hydrangenol-4'-O-β-glucoside, hydramacrophyllol A and B have been isolated from S. tomentosa roots previously [13] .…”
Section: Research Papermentioning
confidence: 99%
“…[18][19][20][21] S. latifolia roots contain terpenes; taraxasteryl myristate, taraxasteryl acetate, motiol, 3-β-hydroxy fern-8 en-7-one acetate, urs-12-en-11-one-3-acetyl, 3-β-hydroxy-fern-7-en-6-one-acetate, olean-12-en-11-one-3-acetyl, fern-7-en-3-β-one, leucodin, β-sitosterol [22][23][24] , phenolic compounds; chlorogenic acid, chlorogenic acid methyl ester, 1,5-dicaffeoyl quinic acid, 3,5-dicaffeoyl quinic acid, methylester of 3,5-dicaffeoyl quinic acid, hydrangenol-8-Oglucoside, hydrangenol-4'-O-glucoside, scorzotomentosin-4'-O-glucoside and a new isocoumarine derivative 25 as well as scorzoveratrin 4'-O-β-glucoside, scorzoveratrin, scorzoveratrozit, 4,5-dicaffeoylquinic acid, 4,5-dicaffeoylquinic acid methyl ester and caffeic acid. 26 Aerial parts of the plant have been reported to contain phenolics which were identified as quercetin-3-O-β-glucoside, hyperoside, hydrangenol-8-Oglucoside, swertisin, 7-methylisoorientin, 4,5-O-dicaffeoylquinic acid, 3,5-di-O-caffeoyl-quinic acid and chlorogenic acid. 27 In the current study, three samples of S. latifolia Fisc.…”
Section: Introductionmentioning
confidence: 99%